The Effects of Iron and Zinc Biofortified Foods on Gut Microbiome, In Vivo (Gallus gallus): Systematic Analysis. (7th June 2021) - Rossi, Robert; Agarwal, Nikita; Cheng, Jacquelyn
Abstract: Objectives: Systematically analyze in-vivo (Gallus gallus) experimental studies that evaluate the effects of Fe and Zn biofortified foods or their derivatives on gut microbiota modulation. Methods: The review was carried out in accordance with the Preferred Reporting Items for Systematic review and Meta-Analysis (PRISMA) guidelines. Two researchers independently performed the data search at PubMed, Web of Science, Science Direct, and Scopus databases for experimental studies conducted in animal models published from January 2010 until December 2020. Five studies from the collection of 592 were selected based on the inclusion and exclusion criteria and analyzed. Results: The studies indicated the dietary consumption of about 50% Fe and Zn biofortified foods provided several health benefits and improved the gut microbiome. Consumption of Fe and Zn biofortified foods was linked to increased abundance and capacity of short chain fatty acids and lactic acid producing bacteria, resulting in improved micronutrient solubility and absorption in the host. Further, a decrease in potentially pathogenic bacteria such as Streptococcus, Escherichia, and Enterobacter was linked to the consumption of Fe and Zn biofortified foods. Conclusions: Dietary deficiencies of iron and zinc are common health concerns worldwide. Bacteria that colonize the gastrointestinal tract depend on micronutrients to maintain their activities, and gut microbiota compositional analysis may be an effective tool to assess host micronutrient status. This review suggests that Fe and Zn biofortified foods utilization positively restructures the gut microbiome and improves micronutrient absorption, thereby improving human health in vulnerable populations and maintaining micronutrient status in healthy populations. Further clinical and animal studies are needed to support the effects mentioned above. Funding Sources: N/A.